MD2 Blockage Protects Obesity‐Induced Vascular Remodeling via Activating AMPK/Nrf2. Issue 9 (20th July 2017) - Wang, Lintao; Han, Jibo; Shan, Peiren; You, Shengban; Chen, Xuemei; Jin, Yiyi; Wang, Jingying; Huang, Weijian; Wang, Yi; Liang, Guang
Abstract : Objective: Obesity and increased free fatty acid (FFA) levels are tightly linked with vascular oxidative stress and remodeling. Myeloid differentiation 2 (MD2), an important protein in innate immunity, is requisite for endotoxin lipopolysaccharide responsiveness. This study shows that palmitic acid (PA) also bonds to MD2, initiating cardiac inflammatory injury. However, it is not clear whether MD2 plays a role in noninflammatory systems such as obesity‐ and FFA‐related oxidative stress involved in vascular remodeling and injury. The aim of this study is to examine whether MD2 participates in reactive oxygen species increase and vascular remodeling. Methods: Male MD2 −/− mice and wild‐type littermates with a C57BL/6 background were fed a high‐fat diet (HFD) to establish obesity‐induced vascular remodeling. Rat aortic endothelial cells (RAECs) and vascular smooth muscle cells (VSMCs) were treated with PA to induce oxidative stress and injury. Results: In vivo, MD2 deficiency significantly reduced HFD‐induced vascular oxidative stress, fibrosis, and remodeling, accompanied with AMP‐activated kinase (AMPK) activation and nuclear factor erythroid (Nrf2) upregulation. In VSMCs and RAECs, inhibition of MD2 by neutralizing monoclonal antibody to MD2 or small interfering RNA knockdown significantly activated the AMPK/Nrf2‐signaling pathway and reduced PA‐induced oxidative stress and cell injury. Conclusions: It was demonstrated that the deletion or inhibition of MD2 protects against HFD/FFA‐induced vascular oxidative stress and remodeling by activating the AMPK/Nrf2‐signaling pathway.